2013
DOI: 10.1007/s10071-013-0627-x
|View full text |Cite
|
Sign up to set email alerts
|

Gaze alternation in dogs and toddlers in an unsolvable task: evidence of an audience effect

Abstract: Dogs have been shown to use human-directed gazing behaviour and gaze alternation in numerous contexts; however, it is still unclear whether this behaviour can be considered an intentional and referential communicative act. In the current study, adult dogs and preverbal toddlers were tested using the classic unsolvable task paradigm, but varying the attentional stance of the participating audience (the experimenter and the caregiver). The aims were to assess (1) whether dogs and toddlers would use gaze alternat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
69
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(80 citation statements)
references
References 48 publications
11
69
0
Order By: Relevance
“…Gaunet and Deputte [6] also suggested that dogs use their position as a local enhancement cue. The direction of human’s attention influenced dogs’ gaze alternations when they faced a potentially scary object or an unsolvable task [37], [38] (criterion d). Finally, one study [7] suggested that dogs persist (criterion e) when they request a toy and receive an unfamiliar object instead, however this study [7] challenged the elaboration of communication (criterion f).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gaunet and Deputte [6] also suggested that dogs use their position as a local enhancement cue. The direction of human’s attention influenced dogs’ gaze alternations when they faced a potentially scary object or an unsolvable task [37], [38] (criterion d). Finally, one study [7] suggested that dogs persist (criterion e) when they request a toy and receive an unfamiliar object instead, however this study [7] challenged the elaboration of communication (criterion f).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, dogs are sensitive to human’s visual perspective [35], [36]: in the presence of an opaque barrier blocking the human’s view of a forbidden food, dogs took more of this forbidden food [35]. The influence of humans' direction of attention on dogs’ communicative signals has been observed when facing a new and potentially scary object [37] and in an unsolvable task [38], but it has not been addressed when dogs can beg for food. Finally, one study investigated the persistence and elaboration of communication in dogs [7]: dogs showed persistence when an unfamiliar object was returned instead of a desirable toy, but no new behaviors were observed after receiving the unfamiliar object.…”
Section: Introductionmentioning
confidence: 99%
“…It should be noted that in water rescue dogs gazing behaviour is reinforced to increase dogs' attention to the owner, but not in the context of problem solving. Whether dogs were gazing to seek for help in solving the task, as proposed in other studies (Cooper et al, 2003;Marshall-Pescini et al, 2013, 2009Miklósi et al, 2003Miklósi et al, , 2000Passalacqua et al, 2013Passalacqua et al, , 2011 and/or were waiting to receive commands and instruction, as they are trained to do, is unclear, thereby warranting further investigation.…”
Section: Discussionmentioning
confidence: 93%
“…Although young dogs also show some human-directed gazing behaviour, this trait seems to be influenced by developmental factors during their ontogeny [4]. In addition, both adult dogs and human toddlers (Homo sapiens) take into account the attentional stance of a human and increase their use of gaze alternations during an 'unsolvable problem' task, indicating the communicative and referential nature of the behavioural outcome in this task [5].…”
Section: Introductionmentioning
confidence: 99%